Dokładność pomiaru RTN odbiornikiem Septentrio Altus Nr2 = Accuracy of RTN measurement in various measurement conditions - Oleniacz, Grzegorz; Skrzypczak, Izabela; Świętoń, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Series of GNSS receiver tests allowed to determine real accuracy of RTN measurements. Repeated measurements allowed to estimate accuracy in function of used navigation satellite system, duration of measurements and field conditions on measurement site which are related to horizon visibility by obstacles (bushes). Research results indicate no dependency between the technology used and the measurement accuracies obtained and significant impact of the conditions on set-up on the measurement's results.
Keywords: GPS; GLONASS; GNSS; Septentrio; system nawigacji satelitarnej; dokładność pomiaru